Globalisation, Competitive Governments, and Constitutional Choice in Europe - Albert Breton; Heinrich Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2002)
The traditional school of economic policy analysis predicts that globalisation will give rise to predatory competition between the governments of the European nation states. The consequence is anticipated to be a marked reduction in, if not the destruction of, the benevolent Welfare State. The objective of this contribution is to present the main arguments that have led us to believe that, this traditional literature notwithstanding, a European constitution should not restrict but rather should encourage horizontal and vertical governmental competition. In our view the European political order, in defining the relationship among member states and also the relationship between the member states and the EU, ought to be inspired by what we know about competition in the commercial sphere.
Keywords: 330; globalisation; globalization